We put the values of a,b,c in the equation given below and we get

\(\frac{2+4}{5} - \frac{5}{2+4}\)

= \(\frac{6}{5} - \frac{5}{6}\)

Now we can take the LCM of the denominators of these fractions and solve it.

But, let's see another method.

We know that \(\frac{6}{5} = 1.2\)

and \(\frac{5}{6}\) is a little less than.

So, 1.2 - (little less than 1) cannot be negative. It can neither be 0 nor 1.

OA, BCarcass wrote:

If \(a = 2\), \(b = 4\), and \(c= 5\), then \(\frac{a+b}{c} - \frac{c}{a+b} =

\)

A. 1

B. 11/30

C. 0

D. -11/30

E. -1

_________________

If you like my solution, do give kudos!